The impact of sustainable development policy on EBIT growth in logistics companies - Gniadkowska-Szymańska, Agata (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
Sustainability has evolved from a corporate social responsibility (CSR) component into a strategic tool for building competitive advantage, particularly in the logistics industry, which intensively utilizes environmental resources and infrastructure. The aim of this article is to examine the impact of ESG policies on EBIT growth in logistics companies in Europe from 2017 to 2023. This study examines the impact of ESG disclosure and its components – environmental, social, and governance – on EBIT growth in European logistics companies over 1-, 2-, 3-, and 5-year time horizons. Distinguishing between air, sea, and land transport companies, the study explores sectorspecific differences in the financial impact of ESG initiatives, addressing a gap in the existing literature, which often focuses on stock market valuation rather than operational performance. The study utilizes heteroscedasticity-corrected OLS models and panel models, enabling the identification of short- and long-term effects. The results show that the implementation of sustainable development policies had a significant impact on EBIT growth, particularly over the 3- and 5-year periods. The strongest effect was observed for the environmental component (EVN), confirming the adoption of pro-environmental measures in the operating system. In maritime transport, the EBIT increase was a result of the synergy of all three ESG elements, while in air transport, the impact of EVN became apparent after just two years. In land transport (rail and road), the ESG effect was visible only in the short term, which may reflect less-developed sustainability strategies in these companies.